The Effects of Guided Imagery on Comfort in Palliative Care - Coelho, Adriana Raquel Neves (2018)
Guided imagery (GI) is a nonpharmacological intervention that is increasingly implemented in different clinical contexts. However, there have been no studies on the effect of GI on the comfort of inpatients of palliative care (PC) units. Therefore, the aim of this study was to evaluate the effects of GI on the comfort of patients in PC. A 1-group, pretest-posttest, pre-experimental design was used to measure differences in heart rate, respiratory rate, pain, and comfort in patients (n = 26) before and after a 2-session GI program. The intervention featuring GI increased comfort, measured by an Abbreviated Holistic Comfort Scale and the visual analog comfort scale (P G .001), and decreased heart rate (P G .001), respiratory rate (P G .001), and pain, as measured by the (numerical) visual analog pain scale (P G .001). This study demonstrates that the use of an intervention featuring GI increases the comfort of oncology patients admitted to a PC unit. The use of GI by nurses is inexpensive, straightforward to implement, and readily available and may result in the provision of comfort care.